Explaining paranoia: cognitive and social processes in the occurrence of extreme mistrust - Daniel Freeman; Bao Sheng Loe (BMJ Mental Health, 2023)
Background Paranoia—incorrectly thinking that others are deliberating trying to harm you—causes distress, undermines social interactions and leads to withdrawal. It presents across multiple psychiatric diagnoses.Objective The primary aim was to determine the extent that cognitive and social processes may explain paranoia. The secondary aim was to identify explanatory factors that distinguished paranoia and social anxiety.Methods 10 382 UK adults, quota sampled to match the population for age, gender, ethnicity, income and region, participated in a non-probability survey. All participants completed a paranoia measure and assessments of cognitive and social processes. Structural equation modelling was conducted.Findings 2586 (24.9%) participants described being mistrustful of other people. 1756 (16.9%) participants wanted help to trust more. 66.7% of variance in paranoia was explained by a model comprising (in descending order of importance): within-situation defence behaviours, negative images, negative self-beliefs, discrimination, dissociation, aberrant salience, anxiety sensitivity, agoraphobic distress, worry, less social support, agoraphobic avoidance, less analytical reasoning and alcohol use. All explanatory factors were associated with paranoia and social anxiety. Ten factors were more closely associated with paranoia than social anxiety, including discrimination, hallucinations, negative images, aberrant salience and alcohol use. Nine factors were more closely associated with social anxiety, including less positive self-belief, an external locus of control, worry and less analytical reasoning.Conclusions Multiple causes are likely to be involved in paranoia. Cognitive and social processes may explain a high degree of paranoia.Clinical implications Multiple clear targets for intervention to reduce paranoia are identified.